ISBD(CR): mednarodni standardni bibliografski opis serijskih publikacij in drugih kontinuiranih virov - Kavčič, Irena (Knjižnica, 2005)
The article presents the new concept of continuing resources, covering serial publications and integrating resources, and describes important, international decisions which derive from the expansion of standard coverage, especially as the consequence of the inclusion of online resources. New and changed provisions included in ISBD(CR) - in comparison with ISBD(S) - and required by the nature of the new resources are described.
Keywords: katalogizacija; bibliografski opis; ISBD(S); ISBD(CR); serijske publikacije; mednarodni standardi